AgNPs incorporated on deacetylated electrospun cellulose nanofibers and their effect on the antimicrobial activity. (15th September 2017) - Kalwar, Kaleemullah; Hu, Lin; Li, Da‐Li; Shan, Dan
Abstract : In the present study, cellulose acetate (CA) nanofibers were prepared by electrospinning technique. Alkaline hydrolysis was introduced for conversion of CA nanofibers to cellulose nanofibers. Nanofibers were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier transform infrared spectroscopy (FTIR). Furthermore, silver nanoparticles (AgNPs) were incorporated on regenerated cellulose nanofibers with different concentrations and used as an antimicrobial agent against Gram negative Escherichia coli BH5 α, Gram positive Spectromyces arenus, and Aspergillus flavus . Strong inhibition activities were determined.